ANALISIS PENGARUH IRADIASI SINAR GAMMA TERHADAP KEKUATAN TARIK DAN PENYERAPAN AIR KOMPOSIT POLYMER BLEND BERPENGUAT SERAT BAMBU - Rifki Hikmawan; Indah Widiastuti; Danar Susilo Wijayanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
The main purpose of this study was to determine the effect of variations in gamma ray dose on the physical and mechanical properties of natural fiber reinforced polymer blend composites. The method used in this research is experimental. This research was conducted on polymer blend composites, namely recycled High Density Polyethylene (rHDPE) and recycled Polypropylene (rPP) with bamboo fiber reinforcement with variations in gamma ray doses of 0 kGy, 25 kGy, 50 kGy, and 75 kGy. Bamboo is processed using a crusher into fibers with a size of 40 mesh and treated with 5% NaOH alkali for 10 minutes then dried using oven for 24 hour at a temperature of 105 °C to remove lignin contained in bamboo fibers. The composite was made using two machines, namely an extrusion machine with a heater temperature of 175 °C, 180 ºC, 185 ºC, and 190 ºC with a screw speed of 25 rpm. Then the injection molding machine with a temperature of 220 ºC with a specimen mold temperature of 90 ºC and an injection pressure of about 45 bar for 20 minutes. Gamma ray treatment was carried out after making the specimen before testing. Where a gamma cell irradiator is used and as a source of gamma rays, cobalt-60 (Co-60) is used. Tensile and water absorption tests are used to determine the physical and mechanical properties of the composite material according to ASTM D638 type V and ASTM D570-98 standards. The test results showed that the higher the dose used, the lower the physical and mechanical properties of the composite. The highest tensile strength was found at the 25 kGy dose treatment of 13.68 MPa and the lowest at the 75 kGy dose treatment. The lowest water content absorption and thickness expansion after 144 hours of immersion were at a 50 kGy gamma dose of 3.43% and 1.27%, respectively. Meanwhile, the highest condition was found at the 75 kGy gamma ray dose of 3.79% and 1.42%, respectively.